An antibiogram classification system based on an hybrid hough transform and gradient approach - Ferreira, Rayssa Lopes Dantas (2011)
The antibiogram performed by the disc diffusion method is a test frequently used in clinical microbiology. In this test, the result is given by the diameter of the inhibition zone formed around the antibiotic disc. In general, this measurement is performed manually. The main objective of this work was to develop an automatic image analysis system to assess the susceptibility of microorganisms to different antibiotics. As a first step, several images of antibiograms were obtained. Subsequently the images were subjected to image processing techniques. After the elimination of noise, the Hough transform was used to detect the antibiotic discs. Next, from the center of each identified disc, the inhibition zone was detected recurring to a gradient method. According to the diameter of the inhibition zone a susceptibility classification was made. The results prove the validity of the developed tool to detect the antibiotics discs and to segment the inhibition zones used in microorganism’s susceptibility evaluation.